The association of paid medical and caregiving leave with the economic security and wellbeing of service sector workers - Julia M. Goodman; Daniel Schneider (BMC Public Health, 2021)
Abstract Background Service-sector workers in the U.S. face extremely limited access to paid family and medical leave, but little research has examined the consequences for worker wellbeing. Our objective was to determine whether paid leave was associated with improved economic security and wellbeing for workers who needed leave for their own serious health condition or to care for a seriously ill loved one. Methods We analyzed data collected in 2020 by the Shift Project from 11,689 hourly service-sector workers across the US. We estimated the impact of taking paid leave on economic insecurity and wellbeing relative to taking unpaid leave, no leave, or not experiencing a need to take leave. Results Twenty percent of workers needed medical or caregiving leave in the reference period. Workers who took paid leave reported significantly less difficulty making ends meet, less hunger and utility payment hardship, and better sleep quality than those who had similar serious health or caregiving needs but did not take paid leave. Conclusions Access to paid leave enables front line workers to take needed leave from work while maintaining their financial security and wellbeing.